Adaptive Data Warehouse as the Technological basis of the banking Ecosystem - E. V. Vasilieva; K. S. Solyanov; T. D. Konevtseva (Финансы: теория и практика)
New guidelines of omnichannel and ecosystem are emerging driven by modern digital transformation of the banking business. To improve customer experience of interaction with banking services more banks are switching to the omnichannel model. In this model, the customer is able to perform operations in a unified interface using any communication methods, and sees no difference in the processes between off-line and on-line operations. This requires changes in a bank’s IT architecture, whose center is a bank data warehouse. The aim of this study is to show the possibility of developing a method for designing a banking data warehouse so that it can be easily adaptable for new business projects and tasks. The authors used the following research methods: analysis, logical modeling of the identified relationships. They developed an adaptive banking data warehouse designer in the environments of SAP PowerDesigner, StarUML, PL/SQL Developer. The article tackles the approach towards development of an adaptive model of a banking data warehouse, based on the principle of splitting data into components. It makes it possible to set the warehouse contours for specific business tasks, combine elements, and expand the structure of the banking data warehouse in the context of its integration with various external software objects. The article highlights the interaction between the components of the banking data warehouse and business tasks, the list of which can be expanded in the context of various bank projects. The article provides a detailed description of the basic set of components of the adaptive banking data warehouse model. This set may serve as the foundation for designing a banking data warehouse for a specific business task. The article provides the data model and attribute composition of the General Ledger component, the data model of the Plastic Cards, Transactions, Applications, Contractors, etc. components, as well as indicates the relationships between the components. The study presents design features of a new type of the banking data warehouse. The authors concentrate on the technological features of creating a unified front-end omnichannel banking system as a separate task. They conclude that the developed basic set of components and business objects of adaptive banking data warehouse will ensure data integrity and reduce design time.